Paleoanthropology And Orthodontıcs - T. Ufuk Toygar Memikoğlu; Hakan Gögen (Turkish Journal of Orthodontics, 1997)

(untitled)
The aim of this study was to evaluate the collaboration of paleoanthropology and orthodontics. Because medicine and dentistry are based on anatomy and/or physical anthropology, the relationship between these areas has been presented in a historical order.